Ultra-high Seebeck coefficient of a thermal sensor through entropic optimisation of ligand length of Fe(ii) spin-crossover (SCO) materials - Che Hassan, Hazirah; Mohd Said, Suhana; Nik Ibrahim, Nik Muhd Jazli; Megat Hasnan, Megat Muhammad Ikhsan; Mohd Noor, Ikhwan Syafiq; Zakaria, Rozalina; Mohd Salleh, Mohd Faiz; Md. Noor, Nur Linahafizza; Abdullah, Norbani (Royal Society of Chemistry, 2021)
In this work, we present a spin-crossover (SCO) complex molecular formulation [Fe(Ln)2](BF4)2 in an electrochemical single couple solution. A Seebeck voltage arises when an electrochemical single couple solution is subjected to a temperature difference, resulting in a single couple reaction at either terminal of the electrochemical cell. The ultrahigh Seebeck coefficients were obtained due to a number of molecular optimisation strategies. The [Fe(L16)2](BF4)2 complex demonstrated a maximum Seebeck coefficient of 8.67 mV K−1, achieved through a six-pronged approach to maximise entropy during the transition from low spin (LS) to high spin (HS) through: (i) a change in spin state, (ii) a change in physical liquid crystalline state, (iii) the spin Seebeck effect, (iv) the kosmotropic and chaotropic effect, (v) the fastener effect and (vi) thermal heat absorbance. A reduction of the Seebeck coefficient to 1.68 mV K−1 during the HS–LS transition at higher temperatures is related to the single spin state transition entropy change. In summary, this paper presents a systematic study to identify the contributing factors in the production of a sensor with an ultrahigh Seebeck coefficient for energy harvesting through the optimisation of its molecular entropy elements.